Eksistensi Notaris Pengganti Dalam Prespektif Stufenbauw Theorie (Studi Pasal 33 Ayat (2) Undang-Undang Nomor 2 tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris) - Burhan Adlansyah; Nabbilah Amir (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Notaries are required to always have accuracy, thoroughness, honesty, caution and excellent body condition. Notaries in carrying out their duties can obtain leave rights. If a Notary is on leave, he is required to appoint a substitute Notary. However, the provisions that apply to the Substitute Notary Public have limitations that only apply to 4 (four) Article provisions, this is contained in the provisions of Article 33 paragraph (2) UUJN. These provisions are considered to be very detrimental to justice and legal uncertainty for Substitute Notaries. The purpose of this research is to examine the existence of the Substitute Notary in the provisions of Article 33 paragraph (2) UUJN. The research method used is normative juridical. The results of the study show that the existence of a substitute notary exists and is needed not only for the benefit of a substitute notary or for a notary who is taking leave, but especially for the benefit of the public who is using the services of a substitute notary The provisions in Article 33 paragraph (2) UUJN do not work effectively and are not in accordance with the legal system in Indonesia which adheres to the tiered ladder theory (stufenbauw theory) from Hans Nawiasky because it is not in accordance with the ideal foundation of Pancasila and is not in accordance with the constitutional mandate that a Substitute Notary is duly to be given the enforcement of the same provisions as the Notary as stipulated in the UUJN because every human being has the right to equal recognition and treatment before the law and so that the provisions in the UUJN can have the effectiveness and nature of legal purposes. Keywords: Notary; Substitute Notary; Existence